2001
DOI: 10.1046/j.1365-2141.2001.03166.x
|View full text |Cite
|
Sign up to set email alerts
|

Complement activation plays a key role in the side‐effects of rituximab treatment

Abstract: Summary. Treatment with rituximab, a chimaeric anti-CD20 monoclonal antibody, can be associated with moderate to severe first-dose side-effects, notably in patients with high numbers of circulating tumour cells. The aim of this study was to elucidate the mechanism of these side-effects. At multiple early time points during the first infusion of rituximab, complement activation products (C3b/c and C4b/ c) and cytokines [tumour necrosis factor alpha (TNF-a), interleukin 6 (IL-6) and IL-8] were measured in five r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
187
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(195 citation statements)
references
References 16 publications
4
187
1
3
Order By: Relevance
“…As already demonstrated in previous papers, 31,32 Rituximab effects rely on complement-and cell-mediated cytotoxicity, which depend on CD55/CD59 levels 33 and on phagocytic activity, respectively. These activities are variable among individuals, and final efficiency on target cells may be different in each patient.…”
Section: Discussionmentioning
confidence: 94%
“…As already demonstrated in previous papers, 31,32 Rituximab effects rely on complement-and cell-mediated cytotoxicity, which depend on CD55/CD59 levels 33 and on phagocytic activity, respectively. These activities are variable among individuals, and final efficiency on target cells may be different in each patient.…”
Section: Discussionmentioning
confidence: 94%
“…Toxicity and efficacy are related to events after binding, which include B cell signaling, complement activation, direct apoptosis, and antibody dependent cellular cytotoxicity [13]. Complement activation and cytokine secretion, in particular, seems to be the causative factors in side effects associated with infusion reactions [14]. Studies have found complement (C3b/c and C4b/c) and cytokine (TNF-a, IL6, and IL8) levels to be elevated after rituximab infusion [2,[14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Complement activation and cytokine secretion, in particular, seems to be the causative factors in side effects associated with infusion reactions [14]. Studies have found complement (C3b/c and C4b/c) and cytokine (TNF-a, IL6, and IL8) levels to be elevated after rituximab infusion [2,[14][15][16]. In particular, TNF-a has been postulated as the main component in the pathogenesis of ILD because of its proinflammatory effects by inducing chemokines, inflammatory mediators, and angiogenic factors [17].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the complement and some inflammatory cytokines (i.e. tumor necrosis factor-alpha) by rituximab may lead to non-specific bystander lysis or inhibition of some stem cells compartments 16,17 . On the other hand, a majority of studies confirm that only CD34+ cell subsets are significantly associated with short-term and long-term hematopoietic reconstitution 18 .…”
Section: Rituximab Does Not Adversely Affect the Stem Cell Mobilizatimentioning
confidence: 99%